Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration duction of the most important foodstuffs had been increasing for some years when the depression set in in 1929; but it was the sudden decline in purchasing power, not increased supplies, which brought the slump in prices and the consequent “gluts.” The Report on Nutrition and Public Health published last year by the League of Nations points out that “the existence of surplus stocks and over-production in general, at certain moments, in certain countries, does not in any way prove that the world produces too much food, or even enough to meet the needs of its population.” If every family in the country were in a position immediately to demand an optimum diet — that is, a diet which cannot be improved in any respect — we should be faced for a time with a problem of under-production, rather than over-production. GOVERNMENT ACTION AND FOOD CONSUMPTION Cuts in Wages, etc. Government action has aggravated the problem. The effect of the “economy cuts” in 1931 is obvious. While certain of the cuts have been restored — e.g., the cuts in wages and standard benefits — the Means Test remains, taking £15 millions per year from the unemployed. There is no doubt that a considerable proportion of that amount would have been spent on food. Social Services Maternity and Child Welfare Authorities have power to provide milk and nourishment for expectant and nursing mothers and young children. While no specific instruction was given during the economy campaign to reduce expenditure on this service, there is no doubt that expenditure was restricted in many areas because of the economy drive. At present out of 421 Maternity and Child Welfare Authorities, 398 supply milk free or below cost price to children, while 11 supply milk at cost price. A considerable number of Authorities provide milk for 17 127/NU/5/5/1/12